Transparent MgAl2O4 spinel fabricated by spark plasma sintering from commercial powders. Issue 15 (15th October 2018) - Zegadi, A.; Kolli, M.; Hamidouche, M.; Fantozzi, G.
Abstract: Three different MgAl2 O4 spinel powders (S25CRX12, S25CRX14 and S30CR) supplied by Baikowski company were sintered by Spark Plasma Sintering and optically characterized for their transparency. The real in-line transmission (RIT), total forward transmission (TFT), total reflection (TR) and diffuse reflection (DR) were measured for all powders sintered between 1250 and 1350 °C with an incremental step of 20 °C. The S25CRX12 powder sintered at T = 1350 °C exhibits the highest RIT (83.6%) at the wavelength of 550 nm which was enhanced by a post-annealing at 1200 °C up to 85%. The TR and DR of the S30CR sample appear to be independent of wavelength and sintering temperature. The TR is around 11% whereas the DR remains insignificant (1–2%). For the two powders S25CRX12 and S25CRX14, the TR and DR vary according to the wavelength and depend substantially on the sintering temperature. Above 1310 °C, the TR and DR remain almost constant (TR ≈ 12% and DR ≈ 1–4%) in the examined wavelength range.